2013
DOI: 10.1111/scs.12063
|View full text |Cite
|
Sign up to set email alerts
|

Caring for people with dementia disease (DD) and working in a private not‐for‐profit residential care facility for people with DD

Abstract: Caring for people with dementia and working in dementia care is described as having both rewarding and unpleasant aspects and has been studied to a minor extent. This study aims to explore care providers' narrated experiences of caring for people with dementia disease (DD) and working in a private not-for-profit residential care facility for people with DD. Nine care providers were interviewed about their experiences, the interviews were recorded, transcribed and analysed using thematic analysis. The analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
63
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(72 citation statements)
references
References 33 publications
1
63
0
1
Order By: Relevance
“…, Venturato & Drew , Ericson‐Lidman et al . ). The ethnicity of the nurse sample was reported in only one study (Pennington et al .…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…, Venturato & Drew , Ericson‐Lidman et al . ). The ethnicity of the nurse sample was reported in only one study (Pennington et al .…”
Section: Resultsmentioning
confidence: 97%
“…, Ericson‐Lidman et al . ) used qualitative description as their research methodology, three studies (Bowers et al . , McGillis‐Hall et al .…”
Section: Resultsmentioning
confidence: 99%
“…This section will present a synthesis of the relevant studies. For 20 of the studies, the researchers focused on the supervisory performance of the regulated nurses, whereas two researchers (Ericson-Lidman, Larsson, & Norberg, 2013;Vogelsmeier, Farrah, Roam, & Ott, 2010) focused on the qualities, which were similar to the described supervisory behaviors of the other researchers so "supervisory performance" was the main construct used to described the results. Table S1 in the online appendix shows the description of the studies included in the review.…”
Section: Resultsmentioning
confidence: 99%
“…Being an effective supervisor required the nurse to be visible (Ericson-Lidman et al, 2013) and available to staff (McGilton et al, 2009) while "conducting a balancing act" of all their responsibilities. Supervisors anticipated unexpected emergencies (Eriksson & Fagerberg, 2008) and efficiently responded to help subordinates with clinical matters (Dellefield, 2008;Siegel et al, 2008).…”
Section: Supervisors Are Accessible and Interactive But Juggle Multipmentioning
confidence: 99%
“…Addressing person-centred care, Ericson-Lidman et al 170 conducted a small-scale interview study among staff (n = 12) at one residential aged care home in Sweden. They found that the concept of person-centred care was poorly defined and there was a lack of staff understanding and little managerial support.…”
mentioning
confidence: 99%